Acute Toxicity Effects of Malathion on Acetyl Choline Esterase Activity in ‘Carassius auratus’ (Linnaeus, 1758) and Botia striata (Narayan Rao, 1920) - Raj, Manju V.; K., Sherin; K., Sheeba; P. S., Sherly (Research Perspective on Biological Science Vol. 2, 2025)
Fishes serve as bio-indicators for water pollution. The increase in pesticide such as Malathion use in response to agricultural demands poses a risk to non-target organisms, including fish. This chapter deals with the study on malathion's impact—a pesticide prevalent in Kerala and other Indian states—on acetylcholinesterase (AChE) activity in Carassius auratus and Botia striata. Both species were exposed to 0.34 ppm malathion for 48, 72, and 96 hours, followed by a 10-day recovery period. AChE activity was measured using Ellman’s method. Statistical analysis of the observation was done using the online Jeffreys's Amazing Statistics Program (JASP). In 7, 6, 5, 4, and 3 ppm concentrations of Malathion, the mortality rate observed was 90, 50, 20, 10, and 5%. Control groups exhibited the highest AChE activity in brain and muscle, with moderate levels in liver and kidney. After 72 hours of exposure, C. auratus showed a significant brain AChE activity decline from 7.2 to 1.8, while B. striata decreased from 5.7 to 1.4. During recovery, C. auratus's activity rose to 5.26, and B. striata's to 4.46 by day 15. However, C. auratus's kidney AChE activity fluctuated, and in B. striata, AChE activity exhibited abnormal recovery patterns. These results underscore malathion's neurotoxic effects on aquatic life and potential environmental and biodiversity risks. The continuous use of another organophosphate pesticide, endosulfan, has caused adverse human health effects, including chromosomal abnormalities and genetic mutations, potentially transmissible across generations. Likewise, the prolonged use of malathion can cause an irreversible hazardous situation. The study highlights the urgent need for regulatory measures to mitigate malathion's environmental and public health risks.